Inguinal Lymph Node Dissection for Advanced Stages of Plantar Melanoma in a Low-Income Country - Ollo Roland Somé; Malick Diallo; Damien Konkobo; Nassirou Yabré; Valentin Konségré; Issouf Konaté; Sidy Ka (Journal of Skin Cancer)
Background. Advanced stages of plantar acral lentiginous melanoma are common in Africa. Inguinal lymph node dissection (ILND) in these cases plays a critical role in disease-free and overall survival. Our study aims to share our experience in ILND for advanced plantar melanomas. Methods and Study Design. Four-year prospective study. Patients. We included all documented cases of advanced stage plantar melanoma with clinically detectable inguinal lymph node metastasis. Twenty-two of 27 patients identified—with mean age 56 years—underwent ILND. Studied Variables. Tumor patterns and stage, surgery, morbidity, oncologic pathology, and evolution were studied. Statistical software assessed the overall survival (OS). Results. Plantar lesions were all excised with a cancer-free margin (3 cm). ILND was performed for 22 patients with visible (n = 11), palpable (n = 7), and ulcerous (n = 4) lymphadenopathies. It was performed through an S-shaped (n = 11) or ellipse-shaped skin incision (n = 11). The tumors were AJCC stage III (n = 18) and IV (n = 2). We found high Breslow index tumor thickness (>3 mm) and an advanced Clark IV stage (n = 20). All operative wounds healed within 46 days (21–90). Wound healing was delayed by suture failure (n = 16), lymphorrhoea (n = 22), and infection (n = 18). After 29 months, three patients had complete remissions, seven had recurrences, and twelve patients had died. The overall survival (OS) at one year was 56%. In two patients with AJCC stage III disease, the OS was better (22 months). Conclusion. In low-income countries, ILND in advanced stages of plantar foot melanoma is a valuable surgical treatment option. Alongside ILND adjuvants, treatment must be available and accessible to improve survival.